The Relationship between DNA and Biophotons - Onofrei, Victoria (New Trends in Psychology, 2024)
Studies confirm that during a frequency impact on the organism, the resonators that respond to the effects are primarily DNA molecules and biophotons. Researcher Michael Meaney's research found that emotional factors also influence the genome. They set processes in motion in the human body. They have different effects at different frequencies. Researchers David A. Jernigan and Samantha Joseph, while studying photons, discovered that they act both as waves and particles and enter the body mainly through the eyes. Electromagnetic or biophotonic energies may or may not be linked. This connection is at least partly under our control. Research has shown that a positive attitude creates a link between electromagnetic and biophoton emissions, which changes DNA and makes the body healthier.